DISCENCY IN PROEJA: RELATIONS OF (IM)PERCEPTION OF THE EJA MODALITY IN INTEGRATION WITH PROFESSIONAL EDUCATION - Pereira, Gabriel Silveira (2024)
This research analyzes and reflects on the perceptions of students from the Professional Education Program Integrated with Basic Education in the Youth and Adult Education Modality (PROEJA), bearing in mind their conceptions and experiences narrated by students of an Integrated Technical Course in this modality at a campus of the Federal Institute of Education, Science and Technology of Rio Grande do Sul (IFRS). The analysis, which originated from a Master's-level study, set out to understand how the specificities of Youth and Adult Education (EJA) are experienced and observed by the students. This is a qualitative, exploratory and descriptive study, using semi-structured interviews as a data production procedure. The data was analyzed using Content Analysis (CA) by Laurence Bardin (2016), which made it possible to draw closer together the conceptions and historical memories of students graduating from the EJA, the National Exam for the Certification of Competences of Young and Adults (ENCCEJA) and regular education.  Among the results that can be observed is the lack of self-awareness on the part of some of these students as an EJA audience in PROEJA, either due to the technical characteristics of the course and/or the context in which it is offered at the Federal Institute, although the words of all the interviewees show specificities that reiterate the experience of EJA classes.